Identification of novel downstream targets of platelet glycoprotein VI activation by differential proteome analysis: implications for thrombus formation - Schulz, Christian; Leuschen, Nina V.; Fröhlich, Thomas; Lorenz, Michael; Pfeiler, Susanne; Gleißner, Christian A.; Kremmer, Elisabeth; Kessler, Mirjam; Khandoga, Alexander G.; Engelmann, Bernd; Ley, Klaus; Maßberg, Steffen; et al. (Blood, 2010)
Platelets play a key role in hemostasis and various diseases including arterial thrombosis. Glycoprotein VI (GPVI) mediates adhesion to collagen structures exposed at sites of vascular injury and subsequent platelet activation. We determined the effects of specific activation of GPVI on the human platelet proteome. Isolated human platelets were stimulated with an activating monoclonal antibody specific for GPVI. Platelet proteins were analyzed by 2-dimensional difference gel electrophoresis (2D-DIGE) and mass spectrometry. We identified 8 differentially abundant proteins associated with cell signaling, metabolism, organization and rearrangement of the cytoskeleton, and membrane trafficking. Differentially abundant proteins included aldose reductase (AR), beta-centractin, charged multivesicular body protein 3, Src substrate cortactin, ERp57, and pleckstrin. Importantly, GPVI-modulated protein abundance was functionally relevant. Correspondingly, AR enzyme activity significantly increased upon GPVI activation and inhibition of AR resulted in reduced platelet aggregation. Furthermore, ERp57 was released upon ligation of platelet GPVI and increased the activity of tissue factor, a major initiator of blood coagulation. In summary, GPVI activation results in differential changes in abundance of platelet proteins, including AR and ERp57, which support platelet aggregation and platelet-dependent coagulation. These results provide further insight into the mechanisms that underlie platelet activation through the GPVI receptor and may help to identify novel pharmacologic targets.